Impact of specialty glass and concrete on gamma shielding in multi-layered PWR dry casks. (January 2017) - Waly, El-Sayed A.; Fusco, Michael A.; Bourham, Mohamed A.
Abstract: There is a strong likelihood that dry casks will be relied upon for many decades to come as the storage system for nuclear spent-fuel high-level waste (HLW), which places importance on robust shielding materials for cask construction. A dry cask with multi-layered shielding has been simulated in MicroShield v9.05 to determine exposure rates due to gamma-rays at the outer cask surface. The cask consists of a 0.27 ft thick stainless steel type 303Cu waste basket, a 0.2 ft thick lead oxide glass shielding layer (named as Glass 6), and a 1.8 ft thick overpack made of a specialty high density concrete (named as Concrete 6). Three spent fuel configurations have been used as photon sources, which include one high burnup (72 GWd/MTU) and two medium burnup (38.6 GWd/MTU) fuels. The cumulative exposure rate over all photon energies from 15 keV to 2 MeV is 6.81E-6 mR/h at the outer cask surface for the high burnup spent fuel. This is roughly one order of magnitude smaller than if the glass layer were replaced with an equivalent thickness of Concrete 6 and is 3–4 orders of magnitude smaller than replacing the specialty concrete with ordinary, standard density concrete. Varying the ratio of the glass thickness to the concrete thickness significantly impacts the shielding effectiveness, which should be considered along with structural and thermal stability for dry cask designs. Highlights: A 3-layer dry cask with specialty lead-oxide glass and blended concrete was simulated. High (72) and medium (38.6) GWd/MTU burnups were used. Cumulative exposure rate over photon energies 15 keV–2.0 MeV is 6.81E-6 mR/hr at the outer cask surface. Varying the ratio of glass to concrete thickness significantly impacts the shielding effectiveness.